Functional divergence and origin of the DAG-like gene family in plants - Luo, Meijie; Cai, Manjun; Zhang, Jianhua; Li, Yurong; Zhang, Ruyang; Song, Wei; Zhang, Ke; Xiao, Hailin; Yue, Bing; Zheng, Yonglian; Zhao, Yanxin; Zhao, Jiuran; et al. (Scientific reports, 2017)
The nuclear-encoded DAG-like ( DAL ) gene family plays critical roles in organelle C-to-U RNA editing in Arabidopsis thaliana . However, the origin, diversification and functional divergence of DAL genes remain unclear. Here, we analyzed the genomes of diverse plant species and found that: DAL genes are specific to spermatophytes, all DAL genes share a conserved gene structure and protein similarity with the inhibitor I9 domain of subtilisin genes found in ferns and mosses, suggesting that DAL genes likely arose from I9-containing proproteases via exon shuffling. Based on phylogenetic inference, DAL genes can be divided into five subfamilies, each composed of putatively orthologous and paralogous genes from different species, suggesting that all DAL genes originated from a common ancestor in early seed plants. Significant type I functional divergence was observed in 6 of 10 pairwise comparisons, indicating that shifting functional constraints have contributed to the evolution of DAL genes. This inference is supported by the finding that functionally divergent amino acids between subfamilies are predominantly located in the DAL domain, a critical part of the RNA editosome. Overall, these findings shed light on the origin of DAL genes in spermatophytes and outline functionally important residues involved in the complexity of the RNA editosome.